The calcineurin–NFATc pathway modulates the lipid mediators in BAL fluid extracellular vesicles, thereby regulating microvascular endothelial cell barrier function - Karpurapu, Manjula; Nie, Yunjuan; Chung, Sangwoon; Yan, Jiasheng; Dougherty, Patrick; Pannu, Sonal; Wisler, Jon; Harkless, Ryan; Parinandi, Narasimham; Berdyshev, Evgeny; Pei, Dehua; Christman, John W. (Frontiers in Physiology, 2024)
Extracellular vesicles (EVs) mediate intercellular communication by transporting biologically active macromolecules. Our prior studies have demonstrated that nuclear factor of activated T cells cytoplasmic member 3 (NFATc3) is activated in mouse pulmonary macrophages in response to LPS. Inhibition of NFATc3 activation by a novel cell-permeable calcineurin peptide inhibitor CNI103 mitigated the development of acute lung injury (ALI) in LPS-treated mice. Although pro-inflammatory lipid mediators are known contributors to lung inflammation and injury, it remains unclear whether the Calcineurin-NFATc pathway regulates EV lipid content and if this content contributes to ALI pathogenesis. In this study, EVs from mouse bronchoalveolar lavage fluid (BALF) were analyzed for their lipid mediators by liquid chromatography in conjunction with mass spectrometry (LC-MS/MS). Our data demonstrate that EVs from LPS-treated mice contained significantly higher levels of arachidonic acid (AA) metabolites, which were found in low levels by prior treatment with CNI103. The catalytic activity of lung tissue cytoplasmic phospholipase A2 (cPLA2) increased during ALI, correlating with increased amount of AA in the EVs. Furthermore, ALI is associated with increased expression of cPLA2, cyclooxygenase 2 (COX2), and lipoxygenases (5-LOX, 12-LOX and 15-LOX) in lung tissue, and pretreatment with CNI103 inhibited the catalytic activity of cPLA2 and the expression of cPLA2, COX, and LOX transcripts. Furthermore, co-culture of mouse pulmonary microvascular endothelial cell (PMVEC) monolayer and NFAT-Luciferase reporter macrophages with BALF EVs from LPS-treated mice increased the PMVEC monolayer barrier permeability and luciferase activity in macrophages. However, EVs from CNI103-treated mice had no negative impact on PMVEC monolayer barrier integrity. In summary, BAL fluid EVs from LPS-treated mice carry biologically active NFATc dependent, AA-derived lipids which play a role in regulating PMVEC monolayer barrier function.